A simulation approach to hotel revenue management training. Issue 5 (19th October 2018) - Cox, Carmen
Abstract Developing well-rounded revenue management professionals is a key challenge for the hotel industry. Traditional approaches toward revenue management training have typically developed sound technical expertise without developing other important business skills. Simulations have been advocated as a solution to deliver holistic revenue management education. This paper aims to identify the learning outcomes achieved through a simulation-based revenue management training program. It reports the learning outcomes of students engaged in a hotel revenue management simulation. Thematic analysis reveals six sets of critical learning outcomes: revenue management strategy; hotel operational knowledge; decision-making ability; value of teamwork; communication skills; and personal readiness for the workforce.